AGIG Chemo-Immunotherapy in Patients With Advanced Pancreatic Cancer: A Single-Arm, Single-Center, Phase 2 Study - Dai, Wangshu; Qiu, Xin; Lu, Changchang; Zou, Zhengyun; Sha, Huizi; Kong, Weiwei; Liu, Baorui; Du, Juan (Frontiers in Oncology, 2021)
Background To date, chemotherapy remains the only effective treatment of unresectable pancreatic adenocarcinoma. In the past few years, the interest in immunological anticancer therapy rises sharply. AGIG is a novel chemo-immunotherapy regimen that combines nab-paclitaxel + gemcitabine chemotherapy with sequential recombinant interleukin-2 (IL-2) and granulocyte-macrophage colony stimulating factor (GM-CSF) therapy. We conducted a single-arm prospective phase II study to determine the efficacy and safety of the first-line treatment of advanced pancreatic cancer with AGIG regimen. Methods Nab-paclitaxel (125 mg/m2) and gemcitabine (1000 mg/m2) were administered intravenously to all patients on days 1 and 8 triweekly, interleukin-2 (1000000U) and GM-CSF (100 µg) were administered subcutaneously on days 3-5 after chemotherapy. The primary end point was ORR by the Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary end points included safety profile, progression-free survival (PFS), overall survival (OS). Patients’ conditions along with the efficacy and safety were assessed every two cycles. Results Between 11/2018 and 01/2020, sixty-four patients were enrolled. In the sixty-four evaluable patients, the disease control rate (DCR) and overall response rate (ORR) were 76.6% and 43.75%, respectively. The median follow-up time was 12.1 (range 7.1–22.4) months. The median PFS was 5.7 (range 1.63–15.8) months. The median OS was 14.2 (range 2.9–22.0) months. The most common adverse event was fever (75%). The incidence of III/IV grade neutropenia was 4.69%. In subgroup analyses, we found that eosinophil count in the blood elevated three times higher than baseline level predicted a longer survival. Conclusions The AGIG chemo-immunotherapy regimen has presented favorable ORR, OS, and manageable toxicities as first-line therapeutic strategy of advanced pancreatic cancer treatment. This regimen may be a novel reliable therapeutic option for patients with preserved performance status. The improvement of treatment efficiency may be related to the activation of non-specific immune response. Clinical Trial Registration https://clinicaltrials.gov/. identifier NCT03768687.